CircRNA in cancer: Fundamental mechanism and clinical potential - Chen, Liang; Shan, Ge (Cancer letters, 2021)
Circular RNAs (CircRNAs) are a class of single-stranded noncoding RNAs that are formed in a circular conformation via non-canonical splicing or back-splicing events. Aberrant expressions of many circRNAs are observed in diverse cancers, indicating their crucial roles in tumorigenesis and tumor development. Recently, several pieces of evidence have revealed that many circRNAs are involved in the promotion or suppression of cancers to varying degrees via different molecular mechanisms. Here in this review, we present a summary of the characteristics, types, biogenesis, and functions of circRNAs, and outline a series of the most recently studied circRNAs and their functional mechanisms in multiple cancer types with future perspectives. With great advances in nucleic acid-based therapeutic tools, circRNAs could be further explored as targetable molecules in future cancer treatments.0 •CircRNAs have significant regulatory and physiological potentials in diverse cancers.•Differentially expressed circRNAs involve in tumorigenesis.•CircRNAs exert their functions through different mechanisms.•Potentially targetable circRNAs are highly promising in future biomedical research.